The association of physical activity against depression among Universiti Putra Malaysia undergraduate medical students-a cross sectional study - Shakira, Lynncilla; Koh, Eugene Boon Yau; Chong, Seng Choi (Universiti Putra Malaysia Press, 2024)
Introduction: The crossroads of mental health and academia particularly in higher education have drawn considerable attention. Research explores how physical activity impacts depression among medical students in higher education where mental health challenges are prevalent due to academic stress. Materials and methods: In an observational cross-sectional study, 251 undergraduate medical students participated by completing questionnaires assessing physical activity and depressive symptoms. The study utilized the International Physical Activity Questionnaire-Long Form and Centre for Epidemiologic Studies Depression Scale. Results: In a study of 251 medical students split into pre-clinical and clinical groups, the latter were older (23.2 vs 20.3 years) and generally had lower physical activity levels, especially in transport, domestic and leisure activities. Pre-clinical students showed higher overall activity. Depression levels differed significantly between groups with clinical student scoring higher (20.2 vs 18.7). Relationships were noted between depression and physical activity, particularly in transport-related activities, walking and total physical activity-higher activity linked to lower depression. However, no significant correlation was found for moderate or vigorous physical activity levels. Conclusion: Study suggest promoting activities like walking and transportation to mitigate depression among medical students, offering strategies to enhance the mental well-being of future healthcare professionals.